2015
DOI: 10.1017/s0954579415000978
|View full text |Cite
|
Sign up to set email alerts
|

Lower structural integrity of the uncinate fasciculus is associated with a history of child maltreatment and future psychological vulnerability to stress

Abstract: The experience of child maltreatment is a significant risk factor for the development of later internalizing disorders such as depression and anxiety. This risk is particularly heightened after exposure to additional, more contemporaneous stress. While behavioral evidence exists for such “stress sensitization,” little is known about the mechanisms mediating such relationships, particularly within the brain. Here we report that the experience of child maltreatment independent of recent life stress, gender, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 78 publications
(77 reference statements)
5
113
1
3
Order By: Relevance
“…No previous studies have tried to quantify the entire WM connectome by applying graph theoretical approaches, constraining an empirical basis from which to inform directional hypotheses. In contrast, building on previous work discussed above [Hanson et al, ; van Harmelen et al, ; Teicher et al, ], we hypothesized that (a) due to the timing of adversity during critical cortical maturation periods (birth to 3 years), children with a history of maltreatment would show global reductions in brain network connectivity, consistent with a systemic and global influence of adversity on WM development, (b) based on previous findings showing structural and functional alterations as well as increased stress‐related vulnerability in the PFC and temporal lobe, we expected group differences in lobar and regional parameters of WM integrity in these a‐priori regions and, (c) global structural network alterations would be associated with indices of HPA‐functioning (basal morning cortisol) as well as measures related to the maltreatment experience and internalizing psychopathology as shown previously by Hanson et al [].…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…No previous studies have tried to quantify the entire WM connectome by applying graph theoretical approaches, constraining an empirical basis from which to inform directional hypotheses. In contrast, building on previous work discussed above [Hanson et al, ; van Harmelen et al, ; Teicher et al, ], we hypothesized that (a) due to the timing of adversity during critical cortical maturation periods (birth to 3 years), children with a history of maltreatment would show global reductions in brain network connectivity, consistent with a systemic and global influence of adversity on WM development, (b) based on previous findings showing structural and functional alterations as well as increased stress‐related vulnerability in the PFC and temporal lobe, we expected group differences in lobar and regional parameters of WM integrity in these a‐priori regions and, (c) global structural network alterations would be associated with indices of HPA‐functioning (basal morning cortisol) as well as measures related to the maltreatment experience and internalizing psychopathology as shown previously by Hanson et al [].…”
Section: Introductionmentioning
confidence: 78%
“…Childhood maltreatment is a major risk factor for children's social, emotional and neural development, rendering these children at high risk for a range of adverse outcomes at all stages of development [MacMillan and Fleming, ]. Indeed, childhood maltreatment has been associated with poorer educational and economic attainment [Zielinski, ], physical and psychological well‐being [Hanson et al, ; Nusslock and Miller, ], as well as impaired social cognition [Flynn et al, ; Puetz et al, ; Puetz et al, ]. There is increasing consensus among researchers that severe stress in the form of childhood maltreatment triggers a cascade of neurobiological changes in the developing brain via the hypothalamic‐pituitary‐adrenal (HPA) axis [Lupien et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a number of studies have found that adversity experienced early in childhood results in delayed cortical development, relative to those who do not experience adversity, as measured by delayed gray matter maturation and decreased cortical thickness within PFC (Hair, Hanson, Wolfe, & Pollak, 2015; Mackey et al, 2015; McLaughlin et al, 2014; Noble et al, 2015), as well as significant reductions in white matter tracts between PFC and other cortical and subcortical regions (Eluvathingal, 2006; Hanson et al, 2013; Hanson, Knodt, Brigidi, & Hariri, 2015; Sheridan, Fox, Zeanah, McLaughlin, & Nelson, 2012). These structural changes are paralleled by worse performance on classic measures of executive functions (see Brito & Noble, 2014; Hackman & Farah, 2009; S. B.…”
Section: Pfc: Revising Assumptionsmentioning
confidence: 99%
“…Since, the structure of the white matter connection between the amygdala and the ventromedial PFC (the uncinate fasciculus) was predictive of adult internalizing symptoms (Hanson, Knodt, Brigidi, & Hariri, 2015) . Therefore, future studies on the neurobiology of resilience after CM may benefit from studying key brain structures and their growth trajectories, as well as the structural connectivity between these regions.…”
Section: Brain Structurementioning
confidence: 99%